Genome size variation in Cape schoenoid sedges (Schoeneae) and its ecophysiological consequences - van Mazijk, Ruan; West, Adam G; Verboom, G Anthony; Elliott, Tammy L; Bureš, Petr; Muasya, A Muthama (American journal of botany, 2024)
PREMISE: Increases in genome size in plants-often associated with larger, low-density stomata and greater water-use efficiency (WUE)-could affect plant ecophysiological and hydraulic function. Variation in plant genome size is often due to polyploidy, having occurred repeatedly in the austral sedge genus Schoenus in the Cape Floristic Region (CFR), while species in the other major schoenoid genus in the region, Tetraria, have smaller genomes. Comparing these genera is useful as they co-occur at the landscape level, under broadly similar bioclimatic conditions. We hypothesized that CFR Schoenus have greater WUE, with lower maximum stomatal conductance (gwmax) imposed by larger, less-dense stomata. METHODS: We investigated relationships between genome size and stomatal parameters in a phylogenetic context, reconstructing a phylogeny of CFR-occurring Schoeneae (Cyperaceae). Species' stomatal and functional traits were measured from field-collected and herbarium specimens. Carbon stable isotopes were used as an index of WUE. Genome size was derived from flow-cytometric measurements of leafy shoots. RESULTS: Evolutionary regressions demonstrated that stomatal size and density covary with genome size, positively and negatively, respectively, with genome size explaining 72-75% of the variation in stomatal size. Larger-genomed species had lower gwmax and C:N ratios, particularly in culms. CONCLUSIONS: We interpret differences in vegetative physiology between the genera as evidence of more-conservative strategies in CFR Schoenus compared to the more-acquisitive Tetraria. Because Schoenus have smaller, reduced leaves, they likely rely more on culm photosynthesis than Tetraria. Across the CFR Schoeneae, ecophysiology correlates with genome size, but confounding sources of trait variation limit inferences about causal relationships between traits.
Keywords: listy rostlin; Genome, Plant; šáchorovité; průduchy rostlin; polyploidy; Genome Size; genome size; Plant Leaves; délka genomu; functional traits; voda; Phylogeny; Water; stomatal size; Cyperaceae; Plant Stomata; fynbos; water‐use efficiency; Cape Floristic Region; fylogeneze; genom rostlinný